Evaluating light intensity, whey concentration, and pH to enhance biomass and biofuel precursor accumulation in Chlorella vulgaris: A kinetic and experimental approach - Montalvo, Daniel (2025)
Finding alternatives to fossil fuels is important to mitigate climate change. This study investigates the development of Chlorella vulgaris under different levels of light intensities, whey, and pH from a Box-Behnken experimental design. Maximum biomass growth and lipids/carbohydrate content were measured as response variables. The aim is to understand how the microalga responds to various environmental conditions to optimize its growth and biofuel precursors accumulation. The modified Gompertz kinetic model was adjusted to experimental data to understand how the studied conditions impact the growth rate. As a response, it reached production of 2.17 gbiomass·L-1 at high level of intensity light, whey, and pH. The experiments indicated that the accumulation of lipids/carbohydrates is directly correlated with light intensity; however, the levels of whey concentration and pH played a different role in the production of these compounds, obtaining 88 mglipid·gbiomass-1 and 14.54 mgcarbohydrate·gbiomass-1. Finally, the results showed that under light stress (continuous lighting, which can affect biomass growth due to the diurnal cycle of light and darkness), a high availability of nutrients, and an adequate pH an antagonistic relationship in the synthesis of lipids and carbohydrates was observed, that is, as the concentration of lipids increases, the concentration of carbohydrates decreases. Indicating that these compounds compete for the same carbon precursor and that the microalga prefers to increase the synthesis of lipids instead of carbohydrates since the energy content of lipids is higher than that of carbohydrates.